Impact of multidisciplinary chart reviews on opioid dose reduction and monitoring practices. (November 2018) - Rivich, Julianna; McCauliff, Jocelyn; Schroeder, Allison
Abstract: Introduction: The Veterans Affairs (VA) Eastern Colorado Health Care System implemented an Opioid Safety Initiative (OSI); this included multidisciplinary chart reviews of patients with chronic, non-malignant pain on high-dose opioid therapy to provide safety recommendations to prescribers through the electronic medical record. Our study objective was to evaluate the impact of these documented recommendations. Outcomes included change in total daily opioid dose, concurrent prescribing of opioids and benzodiazepines, adherence to local VA/Veterans Integrated Service Network (VISN) policy, and monitoring practices. Methods: This retrospective chart review of patients prescribed ≥200 mg of morphine equivalent daily dose (MEDD) collected data from OSI chart reviews conducted between January 1, 2015 and March 31, 2015. Outcomes were assessed during the 12 months following initial review. Primary outcomes included: opioid dose reduction, discontinuation of concurrent benzodiazepines, and adherence to VA/VISN policy, including documentation of signed informed Consent for Long-Term Opioid Therapy for Pain, biannual urine drug screens (UDS), and follow-up every six months with primary opioid prescriber. Results: Of 147 patients meeting inclusion criteria, 50 patients (34%) reduced opioid dose with the baseline median MEDD decreasing from 315 mg to 278 mg. Of the 48 patients prescribed benzodiazepines and opioids, 10 patients discontinued benzodiazepines (21%). Completion of informed consents increased from 31% to 48%, biannual UDS increased from 44% to 61%, and follow-up with opioid prescriber was unchanged. Conclusion: After completion of OSI chart reviews, reduction in opioid dose and concurrent prescribing of benzodiazepines was observed. VA/VISN policy and monitoring adherence also showed improvement. Highlights: Veterans Affairs introduced an Opioid Safety Initiative. Patients on >200 mg morphine equivalent daily dose were reviewed. Chart reviews were performed and recommendations were documented in medical record. Observed reduction in total opioid dose and concomitant benzodiazepine prescribing. Adherence to safety monitoring parameters improved.